Hubungan pengetahuan dengan kesiapsiagaan dalam menghadapi bencana banjir pada siswa siswi - Indriana, Dwi Liza; Trismiyana, Eka; Romayati, Umi (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: A pre-survey conducted by researchers on 10 students found that approximately 7 (70%) still lacked knowledge and preparedness for potential flooding in their neighborhood. Furthermore, it was discovered that SDN 2 Rajabasa does not hold disaster preparedness classes or training. It appears there are still issues with flood preparedness behavior. Purpose: It is known that there is a relationship between knowledge and preparedness in facing flood disasters among students. Method: The type of quantitative research is a cross-sectional approach. The population used is all 5th grade students, namely 94 respondents and the number of samples is 94 respondents with a total sampling technique with a correlation test is the Chi-square test. Result: Of the 94 respondents, the results showed that the majority of knowledge levels were in the good category, namely 58 people (61.7%), while the majority of preparedness levels were in the very ready category, namely 49 people (52.1%). After conducting statistical tests using chi-square, a p-value of 0.000 (p<0.05) was obtained. Conclusion: There is a significant relationship between knowledge and preparedness for flooding among students at SDN 2 Rajabasa Bandar Lampung. It is hoped that the school and teachers will not only implement or explain the theory but also implement it practically through flood disaster training.   Keywords: Knowledge, flood disaster preparedness, elementary school children   Pendahuluan: Hasil pre survey yang dilakukan peneliti pada 10 siswa di didapatkan bahwa, sekitar 7 anak (70%) masih memiliki pengetahuan dan kesiapsiagaan yang kurang untuk menghadapi bencana banjir yang akan terjadi di lingkungan mereka. Selain itu, diketahui bahwa SDN 2 Rajabasa tidak mengadakan kelas atau pelatihan kesiapsiagaan bencana. Sepertinya masih ada masalah dengan perilaku kesiapsiagaan untuk bencana banjir. Tujuan: Untuk mengetahui hubungan pengetahuan dengan kesiapsiagaan dalam menghadapi bencana banjir pada siswa. Metode: Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi yang digunakan seluruh siswa kelas 5 yaitu 94 responden dan jumlah sampel 94 responden dengan teknik total sampling dengan uji korelasi adalah uji Chi-square. Hasil: Sebanyak 94 responden diperoleh hasil, untuk tingkat pengetahuan mayoritas berada pada kategori baik yaitu sebanyak 58 orang (61.7%), sedangkan tingkat kesiapsiagaan mayoritas berada pada kategori sangat siap, yaitu sebanyak 49 orang (52.1%). Setelah dilakukan uji statistik menggunakan chi-square diperoleh nilai p-value sebesar 0.000 (p<0.05). Simpulan: Terdapat hubungan yang signifikan antara pengetahuan dengan kesiapsiagaan dalam menghadapi bencana banjir pada siswa siswi SDN 2 Rajabasa Bandar Lampung. Diharapkan pihak sekolah maupun guru bukan hanya menerapkan atau menjelaskan secara teoritis tetapi juga harus diterapkan secara praktik melalui pelatihan mengenai bencana banjir.   Kata Kunci: Anak Sekolah Dasar; Pengetahuan; Kesiapsiagaan Bencana Banjir.